2014
DOI: 10.1155/2014/123058
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing of a Mung Bean Plant Growth Promoting Strain ofP. aeruginosawith Biocontrol Ability

Abstract: Pseudomonas aeruginosa PGPR2 is a mung bean rhizosphere strain that produces secondary metabolites and hydrolytic enzymes contributing to excellent antifungal activity against Macrophomina phaseolina, one of the prevalent fungal pathogens of mung bean. Genome sequencing was performed using the Ion Torrent Personal Genome Machine generating 1,354,732 reads (6,772,433 sequenced bases) achieving ~25-fold coverage of the genome. Reference genome assembly using MIRA 3.4.0 yielded 198 contigs. The draft genome of PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In our P. aeruginosa panel, the second subgraph obtained for amikacin resistance (min q = 1.37 × 10 −6 ) gathered unitigs mapping to the 3’ region of a DEAD/DEAH box helicase, known to be involved in stress tolerance in P. aeruginosa [ 38 ]. The unitig with the lowest q-value was present in 13 of 47 resistant strains and in only 1 of 233 susceptible strains and represented a C-C haplotype summarising two mutated positions: 2097 and 2103.…”
Section: Resultsmentioning
confidence: 99%
“…In our P. aeruginosa panel, the second subgraph obtained for amikacin resistance (min q = 1.37 × 10 −6 ) gathered unitigs mapping to the 3’ region of a DEAD/DEAH box helicase, known to be involved in stress tolerance in P. aeruginosa [ 38 ]. The unitig with the lowest q-value was present in 13 of 47 resistant strains and in only 1 of 233 susceptible strains and represented a C-C haplotype summarising two mutated positions: 2097 and 2103.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have proved significant role of Sphingomonas and Pseudomonas for plant hosts by increasing plant biomass, improving cadmium uptake, fixing nitrogen and producing phytohormone including gibberellins and indole-3-acetic acid (IAA) Khan et al, 2014;Chen et al, 2014b;Yang et al, 2014). Genomic analysis of some Pseudomonas strains isolated from plants indicated that they uphold the potential to be involved in plant growth promotion, environmental adaptation and antagonism to fungal pathogens (Duan et al, 2013;Illakkiam et al, 2014). Based on our knowledge, there were no report about function analysis on plant-derived endophytic Halomonas and Geobacillus, requiring more efforts to elucidate how they contribute to the host.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that the antagonistic activities against these fungi strains were the result of the proteolytic activity of proteases on the agar media. Proteases activity could be linked to antagonistic activity against fungi test strains by inhibiting the growth of fungal mycelia (Illakkiam et al, 2013;Liu and Yang, 2013). Screening of CFBs from liquid cultures, however, did not result in the inhibition of A. niger, suggesting that the antifungal compound was produced selectively on solid agar medium but not in the fermentation broth.…”
Section: Secondary Screening and Determination Of Micmentioning
confidence: 99%